Peran Quality Time Keluarga Dalam Menangani Anak Berkebutuhan Khusus (ABK) Dalam Perspektif Yohanes 9:2-3 - Marisa Aulia Gea (Jurnal Teologi Injili dan Pendidikan Agama, 2025)
This research examines the role of family quality time in dealing with children with special needs (ABK) from the perspective of John 9:2-3. Based on analysis of the text, this research uses a descriptive qualitative approach with library study methods to collect and analyze data from various relevant sources. The results of the discussion show that children with special needs are God's initial creation, and there is a need for a deep understanding of human diversity and rejection of stigmatization related to children's conditions. In this context, the role of the family is very important in supporting, protecting and treating children with special needs with appropriate love and respect. The perspective of John 9:2-3 shows that the physical or mental condition of children with special needs is not the result of sin, but is an opportunity to demonstrate God's power and demonstrate God's love and deep concern for children. Therefore, implementing the role of family quality time involves several approaches, including giving full attention when together, involving children in family activities, and reading and meditating on the Bible together. So, this approach has great potential to promote the well-being and development of children with special needs, as well as strengthen healthy and inclusive intrafamilial relationships. Thus, the role of family quality time in dealing with children with special needs is important morally and spiritually, as well as in forming a strong foundation for children's growth and happiness in the family context.